Utility of systematic TSHR gene testing in adults with hyperthyroidism lacking overt autoimmunity and diffuse uptake on thyroid scintigraphy. (27th November 2018) - Patel, Kashyap A.; Knight, Bridget; Aziz, Aftab; Babiker, Tarig; Tamar, Avades; Findlay, Joanna; Cox, Sue; Dimitropoulos, Ioannis; Tysoe, Carolyn; Panicker, Vijay; Vaidya, Bijay
Summary: Objective: Patients with hyperthyroidism lacking autoimmune features but showing diffuse uptake on thyroid scintigram can have either Graves' disease or germline activating TSH receptor ( TSHR ) mutation. It is important to identify patients with activating TSHR mutation due to treatment implication, but the overlapping clinical features with Graves' disease make it difficult to discriminate these two conditions without genetic testing. Our study aimed to assess the potential of systematic TSHR mutation screening in adults with hyperthyroidism, showing diffuse uptake on thyroid scintigraphy but absence of TSH receptor antibodies (TRAb) and clinical signs of autoimmunity. Design: A cross‐sectional study of Caucasian adults with hyperthyroidism, managed at three endocrine centres in the South West, UK, from January 2006 to April 2017. Methods: We recruited 78 adult Caucasian patients with hyperthyroidism showing diffuse uptake on 99m Tc‐pertechnetate thyroid scintigraphy but without TRAb and other autoimmune clinical features of Graves' disease (such as thyroid‐associated ophthalmopathy or dermopathy). Genomic DNA of these patients was analysed for variants in the TSHR gene. Results: Genetic analysis identified 11 patients with four variants in TSHR [p.(Glu34Lys), p.(Asp36His), p.(Pro52Thr) and p.(Ile334Thr)]. None of these variants were pathogenic according to the American College of Medical Genetics and Genomics guideline. Conclusions: Activating TSHR mutations are a rare cause of nonautoimmune adult hyperthyroidism. Our study does not support the routine genetic testing in adult patients with hyperthyroidism showing diffuse uptake on scintigraphy but negative TRAb and lacking extrathyroidal manifestations of Graves' disease.